Differences in the responses of melon accessions to fusarium root and stem rot and their colonization by Fusarium oxysporum f. sp. radicis‐cucumerinum. (29th September 2014) - Cohen, R.; Orgil, G.; Burger, Y.; Saar, U.; Elkabetz, M.; Tadmor, Y.; Edelstein, M.; Belausov, E.; Maymon, M.; Freeman, S.; Yarden, O.
<x xml:space="preserve">Abstract</x> Fusarium root and stem rot caused by the fungus Fusarium oxysporum f. sp. radicis‐cucumerinum is a major disease in greenhouse cucumbers. Over the past decade, the disease has been documented in melon greenhouses in Greece, and recently it has been sporadically recorded in greenhouse melons in Israel. Variations in disease response were found among 41 melon accessions artificially inoculated with the pathogen: 10 accessions were highly susceptible (90–100% mortality), 23 exhibited an intermediate response (20–86%) and eight were resistant (0–4%). Two melon accessions – HEM (highly resistant) and TAD (partially resistant) – were crossed with the susceptible accession DUL. The responses of the three accessions and F1 crosses between the resistant and susceptible parents were evaluated. HEM contributed higher resistance to the F1 hybrid than TAD. Roots of susceptible and resistant accessions were 100 and 79% colonized, respectively, following artificial inoculation. However, only susceptible plants showed colonization of the upper plant tissues. Microscopic evaluation of cross sections taken from the crown region of the susceptible DUL revealed profuse fungal growth in the intercellular spaces of the parenchyma and in xylem vessels. In the resistant cultivar HEM, very little fungal growth was detected in the intercellular spaces of the parenchyma, and none in the xylem or any other vascular tissue. Finding resistant accessions may create an opportunity to study the genetics of resistance inheritance and to develop molecular markers that will facilitate breeding resistant melon cultivars.